Gambaran Kesejahteraan Psikologis Tenaga Kesehatan di Lembaga Pemasyarakatan Kota X - Miranda, Aurelia; Harsono, Yudi Tri (Flourishing Journal, 2025)
This study aims to provide a comprehensive understanding of the psychological well-being of healthcare workers in the X City Correctional Institution. This study uses a qualitative method with a phenomenological approach; the interviews used are semi-structured and conducted with five participants who have worked for more than 5 years. The study is guided by Ryff's six dimensions of psychological well-being. Thematic data analysis and member checks ensure validity. The results of the analysis show that optimal psychological well-being of health workers is reflected in a positive attitude towards themselves and their work, opportunities for self-development, meaning of work, and harmonious relationships. Conversely, suboptimal psychological well-being is characterized by negative views, job discomfort, limited development opportunities, career ambiguity, poor interpersonal relationships, lack of autonomy, and difficulty managing patient burden and interactions. In conclusion, the psychological well-being of health workers in correctional institutions is influenced by the complex interaction of individual characteristics, work environment, self-development, interpersonal relationships, training programs, and adequate resource support. AbstrakPenelitian ini bertujuan untuk mendapatkan gambaran komprehensif mengenai kesejahteraan psikologis tenaga kesehatan di Lembaga Pemasyarakatan Kota X. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi, metode yang digunakan adalah wawancara semi-terstruktur dengan lima partisipan yang telah bekerja lebih dari 5 tahun. Penelitian ini berpedoman pada enam dimensi kesejahteraan psikologis Ryff. Analisis data dengan analisis tematik dan member check memastikan validitas. Hasil penelitian menunjukkan bahwa kesejahteraan psikologis tenaga kesehatan yang optimal tercermin dari sikap positif terhadap diri dan pekerjaan, peluang pengembangan diri, makna kerja, serta hubungan harmonis. Sebaliknya, kesejahteraan psikologis yang kurang optimal ditandai dengan pandangan negatif, ketidaknyamanan kerja, kesempatan pengembangan terbatas, ketidakjelasan karir, hubungan interpersonal buruk, kurangnya otonomi, kesulitan mengelola beban, dan interaksi pasien. Dapat disimpulkan bahwa Kesejahteraan psikologis tenaga kesehatan di lembaga pemasyarakatan dipengaruhi oleh interaksi kompleks antara karakteristik individu, lingkungan kerja, peluang pengembangan diri, hubungan interpersonal, serta program pelatihan dan dukungan sumber daya yang memadai. Faktor-faktor tersebut secara kolektif berkontribusi terhadap peningkatan kesejahteraan psikologis tenaga kesehatan di lembaga pemasyarakatan.